Voronoi diagram based simulation and experimental validation of austenite in C22 and C35 steels - S, Sanchu; N, Biju; Namboothiri, V. N.N. (Metallurgical and Materials Engineering, 2020)
This paper examines the ability of power Voronoi diagram assisted simulation in microstructure modeling during heat treatment. A model is developed for predicting fraction of austenite evolved during continuous heating of steel to austenite range, by integrating geometrical features of power Voronoi diagram and classical nucleation theory. From the simulation results, it is possible to predict the transformed fraction. The simulation results are validated using experiments conducted on two varieties of steels. The maximum error obtained is 2.08%. Thus, power Voronoi assisted simulation can be considered as an effective tool in modeling microstructure evolution during austenitization.